Charles V in context : the making of a European identity - Boone, Marc, 1955-; Demoor, Marysa, 1956- (Gent : Ghent university, 2003)
Marnef (G -) - Charles V's religious policy and the Antwerp Market - Blockmans (W -) - Logistics of warfare in Central Italy, 1527-1530 - Vermeir (R -) - La construction de l' empire - l' origine des transformations institutionelles en Espage au XVIe siècle - Kamen (H -) - Expanding worlds: the gains and losses for local communities - Spanoghe (S -) - Imperialising the Amerindian Other - Between forced integration and dual citizenship - Arnade (P -) - Privileges and the political imagination in the Ghent revolt of 1539 - te Brake (W -) - Charles V and his contitious subjects - De Grauwe (L -) - Quelle langue Charles V parlait-il? Belsey (C -) Tarquin dispossesses: expropriation and consent in 'the rape of Lucrece' - Pieters (J -) - Normality, deviancy and critique - Toward a 'governmental' rreading of Shakespeare's measure for measure - Heene (K -) - Was medieval madness gendered? A case-study on deviant behaviour in the 12th and 13th century - De Hemptinne (T -) - Jeanne de Castille, une reine entre folie et pouvoir (1479-1555) - Denecker (G -) - Making her crazy? The labelling of mental illness and the case of Charlotte of Belgium (1840-1927) - Pinxten (C -), Cornelis (M -), De Munter (K -), Longman (C -), Orye (L -), Renty (P -), Verstraete (G -) - Charles V and european empire-building today - Van Londen (S -), De Ruijter (A -) - Citizenship in the new Europe - Nader (L -) - Fragments of identity, power and control - Genet (J-P -) - Charles V: entre empire et état moderne, un rêve impossible?
Includes bibliographical references.
Bijdragen in het Engels en het Frans
English, French, and Dutch.
Keywords: Charles -- V, -- Holy Roman Emperor, -- 1500-1558.; Group identity -- Europe; Europe -- History -- 1517-1648.; Holy Roman Empire -- History -- Charles V, 1519-1556.; Holy Roman Empire -- Kings and rulers -- Biography